Absorbable bone plate with osteoinductive activity and preparation method and application thereof
Patent Information
- Application Number
- CN202611162802.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-16
AI Technical Summary
即便将上述两种技术手段简单叠加,仍无法解决以下技术缺陷:一是BMP-2直接涂布于材料表面存在明显的突释效应,24 h突释率可达40%以上,且体内半衰期短,难以匹配骨折修复的时间窗;二是PLA降解过程中持续释放乳酸,导致局部微环境pH降至5.5以下,易造成BMP-2蛋白变性失活,大幅降低成骨诱导效率;三是单纯BMP-2诱导的新生骨组织血管化程度不足,深部骨修复速度慢,且骨折断端早期出血、血肿机化周期长,进一步延缓骨愈合进程
本发明提供一种具有骨诱导活性的可吸收接骨板,利用白及多糖优异的成膜性与分子氢键网络,在接骨板表面构建致密的三维网状亲水基质,将BMP-2分子包裹于网络间隙中,使24小时突释率控制在18%以内、4周累计释放约72%,匹配骨折修复早期成骨时间,同时多糖的空间位阻效应减少蛋白酶降解,延长局部作用时长并降低大剂量BMP-2的异位骨化风险。针对PLA降解产酸导致BMP-2变性的行业难题,白及多糖所含糖醛酸羧基形成天然弱酸缓冲体系,将涂层微环境pH稳定在6.5~7.4,使BMP-2体内生物活性保留率提升65%以上,解决了PLA基材料与蛋白因子的兼容问题。白及多糖自身可上调BMP受体表达、抑制负调控因子Smurf1,与外源性BMP-2产生协同效应,成骨活性显著高于两者单独作用之和,且在BMP-2用量减半条件下,诱导效果仍优于全量单纯BMP-2涂层,从而降低大剂量生长因子带来的异位骨化风险。此外,白及多糖可缩短凝血时间约49.5%,减少骨折断端出血与血肿机化周期,并上调VEGF促进新生血管形成,弥补单纯BMP-2血管化不足的缺陷,加速骨痂成熟与力学恢复。该复合功能涂层为纳米级薄层,不影响基体力学性能,材料弯曲强度最高达191.6 MPa,缺口冲击强度为6.2 kJ/m²,可满足四肢非承重及半承重部位骨折的固定需求。
Smart Images

Figure CN122912178A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of bone repair materials technology, and particularly relates to an absorbable bone plate with osteoinductive activity, its preparation method and application. Background Technology
[0002] Fracture repair and reconstruction is a long-standing and important issue in orthopedic clinicians. Currently, commonly used metallic internal fixation materials (such as titanium alloy plates and screws) have long dominated the field of orthopedic internal fixation due to their superior mechanical properties. However, the elastic modulus of metallic internal fixation devices differs significantly from that of bone tissue, easily causing stress shielding effects and affecting the local bone reconstruction process. Furthermore, long-term retention of metallic implants can lead to problems such as foreign body sensation, discomfort from cold stimulation, and imaging artifacts; some patients may require secondary removal, increasing medical costs and the risk of postoperative complications.
[0003] Polylactic acid (PLA) and its copolymers have been widely used in research on absorbable internal fixation materials for orthopedics due to their good biocompatibility, processability, and biodegradability. However, PLA materials alone have limitations such as insufficient mechanical strength and toughness, accumulation of local acidic products during degradation, and lack of active osteogenic induction ability, making them difficult to apply to fracture fixation in load-bearing sites.
[0004] Existing technologies have disclosed the introduction of bioactive glass fibers into PLA matrices to improve the material's mechanical properties and bioactivity. Other existing technologies disclose the loading of bone morphogenetic protein-2 (BMP-2) onto the material surface to enhance osteogenic induction. However, even simply combining these two techniques fails to address the following technical shortcomings: First, direct application of BMP-2 to the material surface exhibits a significant burst release effect, with a 24-hour burst release rate exceeding 40%, and a short in vivo half-life, making it difficult to match the time window for fracture repair. Second, the continuous release of lactic acid during PLA degradation causes the local microenvironment pH to drop below 5.5, easily leading to BMP-2 protein denaturation and inactivation, significantly reducing osteogenic induction efficiency. Third, BMP-2-induced new bone tissue exhibits insufficient vascularization, slow deep bone repair, and prolonged early bleeding and hematoma organization at fracture ends, further delaying the bone healing process.
[0005] Currently, there is no solution that can simultaneously address the aforementioned multiple pain points. Therefore, developing a novel absorbable bone plate that combines high strength and toughness mechanical properties, controllable BMP-2 release, acid-base buffering capacity, and pro-vascular hemostasis function is of great significance for promoting the clinical application of fracture repair materials. Summary of the Invention
[0006] In view of this, the purpose of the present invention is to provide an absorbable bone plate with osteoinductive activity, its preparation method and application.
[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: The present invention provides an absorbable bone plate with osteoinductive activity, comprising an absorbable matrix and a composite functional coating loaded on the surface of the absorbable matrix. The absorbable matrix includes polylactic acid and bioactive glass; The composite functional coating includes bone morphogenetic protein-2 and Bletilla striata polysaccharide; The mass ratio of polylactic acid to bioactive glass is 50~100:10~30; The dry weight loading of the Bletilla striata polysaccharide is 0.1~1.0 mg / cm², and the loading of bone morphogenetic protein-2 is 0.5~3.0 μg / cm².
[0008] Preferably, the diameter of the bioactive glass is 10~20μm.
[0009] Preferably, the bioactive glass is dispersed in polylactic acid.
[0010] Preferably, the bioactive glass comprises 45S5 bioactive glass.
[0011] Preferably, the polylactic acid includes L-polylactic acid with a viscosity-average molecular weight of 100,000 to 200,000.
[0012] This invention provides a method for preparing the absorbable bone plate, comprising the following steps: 1) After mixing polylactic acid with bioactive glass, the mixture is melt-blended and then shaped to obtain an absorbable matrix; 2) Mix Bletilla striata polysaccharide with a buffer solution of pH 7.2-7.4 to obtain a Bletilla striata polysaccharide solution; 3) Mix Bletilla striata polysaccharide solution with bone morphogenetic protein-2 to obtain a composite coating solution; 4) The composite coating liquid is applied to the surface of the absorbable substrate and then freeze-dried under vacuum to obtain an absorbable bone plate with osteoinductive activity.
[0013] Preferably, the melt blending temperature in step 1) is 170~190℃ and the rotation speed is 80~120 rpm.
[0014] Preferably, the buffer solution in step 2) includes PBS buffer; The concentration of Bletilla striata polysaccharide in the solution is 20-50 g / L.
[0015] Preferably, the vacuum freeze-drying temperature in step 4) is -50~-40℃, and the vacuum freeze-drying time is 15~20h.
[0016] This invention provides the application of the absorbable bone plate described above or any of the preparation methods of absorbable bone plate in the preparation of fracture repair materials.
[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention provides an absorbable bone plate with osteoinductive activity. Utilizing the excellent film-forming properties and molecular hydrogen bond network of Bletilla striata polysaccharides, a dense three-dimensional hydrophilic network matrix is constructed on the surface of the bone plate, encapsulating BMP-2 molecules within the network gaps. This results in a 24-hour burst release rate controlled below 18% and a cumulative release of approximately 72% over 4 weeks, matching the early osteogenic time of fracture repair. Simultaneously, the steric hindrance effect of the polysaccharides reduces protease degradation, prolongs the duration of local action, and reduces the risk of ectopic ossification from high-dose BMP-2. Addressing the industry challenge of BMP-2 denaturation due to PLA degradation and acid production, the uronic acid carboxyl groups in Bletilla striata polysaccharides form a natural weak acid buffer system, stabilizing the pH of the coating microenvironment at 6.5–7.4. This increases the in vivo bioactivity retention rate of BMP-2 by over 65%, resolving the compatibility issue between PLA-based materials and protein factors. Bletilla striata polysaccharide can upregulate BMP receptor expression and inhibit the negative regulator Smurf1, producing a synergistic effect with exogenous BMP-2. Its osteogenic activity is significantly higher than the sum of the effects of either agent alone. Even with half the BMP-2 dosage, its induction effect is still superior to a full-dose BMP-2 coating, thus reducing the risk of ectopic ossification associated with high-dose growth factors. Furthermore, Bletilla striata polysaccharide can shorten clotting time by approximately 49.5%, reducing bleeding at fracture ends and the period of hematoma organization. It also upregulates VEGF to promote angiogenesis, compensating for the insufficient vascularization of BMP-2 alone and accelerating callus maturation and mechanical recovery. This composite functional coating is a nanoscale thin layer that does not affect the mechanical properties of the matrix. The material has a maximum flexural strength of 191.6 MPa and a notched impact strength of 6.2 kJ / m², meeting the fixation requirements for fractures in non-weight-bearing and semi-weight-bearing areas of the limbs. Attached Figure Description
[0018] Figure 1 The absorbable bone plate with osteoinductive activity prepared in Example 1 is a finished product. Detailed Implementation
[0019] The present invention provides an absorbable bone plate with osteoinductive activity, comprising an absorbable matrix and a composite functional coating loaded on the surface of the absorbable matrix. In this invention, the absorbable matrix comprises polylactic acid and bioactive glass. The polylactic acid preferably comprises L-polylactic acid with a viscosity-average molecular weight of 100,000 to 200,000. The bioactive glass preferably comprises 45S5 bioactive glass, and the diameter of the bioactive glass is preferably 10 to 20 μm, more preferably 12 to 18 μm, and even more preferably 15 μm. The mass ratio of polylactic acid to bioactive glass is preferably 50 to 100:10 to 30, more preferably 60 to 90:15 to 25, and even more preferably 75:20. The bioactive glass is preferably uniformly dispersed in the polylactic acid.
[0020] In this invention, the composite functional coating comprises bone morphogenetic protein-2 and Bletilla striata polysaccharide; the dry weight loading of the Bletilla striata polysaccharide is 0.1~1.0 mg / cm², preferably 0.3~0.8 mg / cm², more preferably 0.5 mg / cm²; the loading of bone morphogenetic protein-2 is 0.5~3.0 μg / cm², preferably 1.0~2.5 μg / cm², more preferably 2.0 μg / cm², and the bone morphogenetic protein-2 is preferably uniformly dispersed in the Bletilla striata polysaccharide.
[0021] This invention provides a method for preparing the absorbable bone plate, comprising the following steps: 1) After mixing polylactic acid with bioactive glass, the mixture is melt-blended and then shaped to obtain an absorbable matrix; 2) Mix Bletilla striata polysaccharide with a buffer solution of pH 7.2-7.4 to obtain a Bletilla striata polysaccharide solution; 3) Mix Bletilla striata polysaccharide solution with bone morphogenetic protein-2 to obtain a composite coating solution; 4) The composite coating liquid is applied to the surface of the absorbable substrate and then freeze-dried under vacuum to obtain an absorbable bone plate with osteoinductive activity.
[0022] In this invention, polylactic acid is mixed with bioactive glass, melt-blended, and then shaped to obtain an absorbable matrix. The melt-blending temperature is preferably 170~190℃, more preferably 175~185℃, even more preferably 180℃, and the rotation speed is preferably 80~120 rpm, more preferably 90~110 rpm, even more preferably 100 rpm. After shaping, the process preferably includes grinding, polishing, and sterilization steps.
[0023] In this invention, Bletilla striata polysaccharide is mixed with a buffer solution to obtain a Bletilla striata polysaccharide solution; the buffer solution preferably includes PBS buffer, and the pH of the buffer solution is 7.2~7.4, preferably 7.3; the mixing temperature is preferably 0~6℃, more preferably 2~5℃, and even more preferably 4℃; the concentration of Bletilla striata polysaccharide in the Bletilla striata polysaccharide solution is preferably 20~50 g / L, more preferably 25~40 g / L, and even more preferably 30 g / L.
[0024] In this invention, a Bletilla striata polysaccharide solution is mixed with bone morphogenetic protein-2 to obtain a composite coating liquid; the mixing time is preferably 15-60 min, more preferably 20-45 min, and even more preferably 30 min; the mixing speed is preferably 30-120 rpm, more preferably 60-90 rpm, and even more preferably 75 rpm.
[0025] In this invention, a composite coating liquid is applied to the surface of an absorbable substrate and then vacuum freeze-dried to obtain an absorbable bone plate with osteoinductive activity. The vacuum freeze-drying temperature is preferably -50~-40℃, more preferably -48~-42℃, and even more preferably -45℃. The vacuum freeze-drying time is preferably 15~20h, more preferably 17~19h, and even more preferably 18h. The above operation is repeated 1~3 times until the coating load reaches the target value.
[0026] This invention provides the application of the absorbable bone plate described above or any of the preparation methods of absorbable bone plate in the preparation of fracture repair materials.
[0027] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0028] Source of materials
[0029] Bletilla striata polysaccharide was purchased from Pusitang Biotechnology Co., Ltd. Bone morphogenetic protein-2 was purchased from Thermo Fisher Scientific. PBS buffer was purchased from Thermo Fisher Scientific; 45S5 bioactive glass fiber and L-polylactic acid granules were purchased from Beijing Naton Technology Group Co., Ltd. The bioactive glass fiber has a length of 3mm and a diameter of 12~15μm.
[0030] Example 1
[0031] Weigh 80 kg of L-polylactic acid granules and 20 kg of 45S5 bioactive glass fiber, mix them evenly at high speed, and then add them to a twin-screw extruder. Melt blend and granulate at 180°C and 100 rpm (after twin-screw melt blending, the average residual length of 45S5 bioactive glass fiber in the matrix is 150~200 μm). Add the resulting granules to an injection molding machine and injection mold them at 185°C to form bone plate sample blanks. After surface polishing, sterilize with ethylene oxide for later use to obtain an absorbable matrix.
[0032] Bletilla striata polysaccharide was dissolved in PBS buffer at pH 7.4 and stirred at 4°C until completely dissolved to obtain a Bletilla striata polysaccharide solution with a concentration of 30 g / L. BMP-2 was added to the Bletilla striata polysaccharide solution and stirred at 60 rpm for 30 min until uniformly dispersed, so that the concentration of BMP-2 was 0.12 g / L, thus obtaining the composite coating solution.
[0033] The sterilized absorbable substrate is immersed in the composite coating solution for 45 seconds, then removed and excess liquid is absorbed with filter paper. It is then pre-frozen at -20°C for 2 hours, followed by drying at -45°C for 18 hours. This immersion and freeze-drying process is repeated once to achieve the target coating loading (0.5 mg / cm² for Bletilla striata polysaccharide and 2.0 μg / cm² for BMP-2), yielding the final product (e.g., ...). Figure 1 ).
[0034] Example 2
[0035] The mass of L-polylactic acid was adjusted to 85 kg, and the mass of 45S5 bioactive glass fiber was adjusted to 15 kg; based on the surface area of the bone plate, the dry weight loading of Bletilla striata polysaccharide in the composite functional coating was 0.3 mg / cm², and the loading of BMP-2 was 1.0 μg / cm²; the mass concentration of the polysaccharide solution was 2%. Other aspects were the same as in Example 1.
[0036] Example 3
[0037] The mass of polylactic acid (PLA) was adjusted to 75 kg, and the mass of 45S5 bioactive glass fiber was adjusted to 25 kg; the dry weight loading of Bletilla striata polysaccharide in the composite functional coating was 0.8 mg / cm², and the loading of BMP-2 was 3.0 μg / cm²; the mass concentration of the polysaccharide solution was 5%. Other parameters were the same as in Example 1.
[0038] Example 4
[0039] The mass of polylactic acid (PLA) was adjusted to 80 kg, and the mass of 45S5 bioactive glass fiber was adjusted to 20 kg; the dry weight loading of Bletilla striata polysaccharide in the composite functional coating was 0.5 mg / cm², and the loading of BMP-2 was 1.0 μg / cm²; the mass concentration of the polysaccharide solution was 5%. Other aspects were the same as in Example 1.
[0040] Comparative Example 1
[0041] Pure L-polylactic acid bone plate, without added bioactive glass fiber, and without surface coating; its absorbable matrix and preparation process are the same as in Example 1.
[0042] Comparative Example 2
[0043] Weigh 80 kg of L-polylactic acid granules and 20 kg of 45S5 bioactive glass fiber, without surface coating; the preparation process of its absorbable matrix is the same as in Example 1.
[0044] Comparative Example 3
[0045] 80 kg of L-polylactic acid granules and 20 kg of 45S5 bioactive glass fiber were weighed and coated with BMP-2 only, without any Bletilla striata polysaccharide. The loading of BMP-2 was 2.0 μg / cm², and the rest was the same as in Example 1. The fiber was prepared by direct dip-coating-freeze-drying method.
[0046] Comparative Example 4
[0047] 80 kg of L-polylactic acid granules and 20 kg of 45S5 bioactive glass fiber were weighed and coated with only Bletilla striata polysaccharide, without BMP-2. The loading of Bletilla striata polysaccharide was 0.5 mg / cm², and the rest was consistent with Example 1. The fiber was prepared by direct dip-coating-freeze-drying method.
[0048] Experimental Example 1
[0049] System performance tests were conducted on the above-described embodiments and comparative samples. Five parallel samples were tested in each group, and the average value of the results was taken. The test methods and results are as follows: (1.1) Mechanical property test: The three-point bending strength and bending modulus were tested according to GB / T 9341-2008 standard, and the notched impact strength of the simply supported beam was tested according to GB / T 1843-2008. The results are shown in Table 1.
[0050] Table 1 Comparison of mechanical properties of each group of samples
[0051] The results in Table 1 show that as the proportion of bioactive glass fiber increases, the flexural strength, modulus, and impact toughness of the matrix all increase simultaneously. The thin surface coating has no significant negative impact on the overall mechanical properties of the matrix, and the material of this invention maintains excellent mechanical load-bearing capacity. There are no statistically significant differences in the mechanical properties of all coated groups compared with Comparative Example 2, proving that the surface coating does not degrade the high strength and toughness characteristics of the matrix.
[0052] (1.2) pH test of the microenvironment for in vitro degradation: Each group of samples was immersed in PBS buffer at 37℃ and pH 7.4 with a solid-liquid ratio of 1 g: 20 mL. Fresh buffer was replaced weekly. The pH value of the immersion solution was tested in the 4th week of degradation. The results are shown in Table 2.
[0053] Table 2 Comparison of pH values of soaking solution after 4 weeks of degradation
[0054] The results showed that the Bletilla striata polysaccharide coating could significantly buffer the acidic environment generated by PLA degradation, and the buffering capacity increased with the increase of Bletilla striata polysaccharide loading. It could stabilize the local pH in the physiological neutral range, providing suitable conditions for maintaining BMP-2 protein activity and cell growth.
[0055] (1.3) BMP-2 in vitro release behavior test: The release of BMP-2 from the sample in PBS buffer at 37℃ was detected by ELISA. The burst release rate at 24 h and the cumulative release rate at 28 days were tested. The results are shown in Table 3.
[0056] Table 3 Comparison of BMP-2 in vitro release performance
[0057] The results showed that the network matrix formed by Bletilla striata polysaccharides could significantly inhibit the initial burst release of BMP-2 and prolong the release period; the higher the polysaccharide loading, the more obvious the sustained release effect, and a stable and continuous release behavior could be achieved.
[0058] (1.4) In vitro osteogenic activity test: Rat bone marrow mesenchymal stem cells (rBMSCs) were cultured in vitro. The alkaline phosphatase (ALP) activity after 7 days of culture and the alizarin red mineralization quantification after 14 days of culture were detected. The results were normalized based on the detection values of Comparative Example 2 (100%). The results are shown in Table 4.
[0059] Table 4 Comparison of in vitro osteogenic activity
[0060] Normalization was performed based on Comparative Example 2 (100%):
[0061] The results showed that, under the same BMP-2 loading, the osteogenic activity of Example 1 was significantly higher than that of Comparative Example 3, confirming a significant synergistic osteogenic effect between Bletilla striata polysaccharide and BMP-2; moreover, the osteogenic activity increased synchronously with the increase of both Bletilla striata polysaccharide and BMP-2 loading, exhibiting a good dose-response relationship. The ALP and mineralization levels of Example 4 were significantly higher than those of Comparative Example 3 with full BMP-2, confirming that better osteogenic effects can be achieved with reduced growth factor dosage.
[0062] (1.5) In vitro coagulation time test: Fresh rabbit whole blood was used for in vitro coagulation test, and the coagulation time on the surface of each group of samples was recorded. The results are shown in Table 5.
[0063] Table 5 Comparison of in vitro coagulation time and VEGF secretion
[0064] The results showed that the Bletilla striata polysaccharide coating endowed the material with excellent hemostatic properties, significantly shortened the clotting time, and the hemostatic effect increased with the increase of polysaccharide loading, which is beneficial to early hemostasis and hematoma organization at the fracture ends.
[0065] In summary, this invention, by introducing Bletilla striata polysaccharide to construct a composite functional coating, simultaneously achieves multiple effects such as sustained release and stabilization of BMP-2, buffering of acidic microenvironment, osteogenic synergy, promotion of angiogenesis, and hemostasis. While maintaining high strength and toughness mechanical properties, it significantly enhances the bone repair activity of the material, demonstrating outstanding inventiveness and clinical application value.
[0066] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. An absorbable bone plate with osteoinductive activity, characterized in that, It includes an absorbable substrate and a composite functional coating loaded on the surface of the absorbable substrate; The absorbable matrix includes polylactic acid and bioactive glass; The composite functional coating includes bone morphogenetic protein-2 and Bletilla striata polysaccharide; The mass ratio of polylactic acid to bioactive glass is 50~100:10~30; The dry weight loading of the Bletilla striata polysaccharide is 0.1~1.0 mg / cm², and the loading of bone morphogenetic protein-2 is 0.5~3.0 μg / cm².
2. The absorbable bone plate according to claim 1, characterized in that, The diameter of the bioactive glass is 10~20μm.
3. The absorbable bone plate according to claim 2, characterized in that, The bioactive glass is dispersed in polylactic acid.
4. The absorbable bone plate according to claim 3, characterized in that, The bioactive glass includes 45S5 bioactive glass.
5. The absorbable bone plate according to claim 1, characterized in that, Polylactic acid includes L-polylactic acid, with a viscosity-average molecular weight of 100,000 to 200,000.
6. The method for preparing the absorbable bone plate according to any one of claims 1 to 5, characterized in that, Includes the following steps: 1) After mixing polylactic acid with bioactive glass, the mixture is melt-blended and then shaped to obtain an absorbable matrix; 2) Mix Bletilla striata polysaccharide with a buffer solution of pH 7.2-7.4 to obtain a Bletilla striata polysaccharide solution; 3) Mix Bletilla striata polysaccharide solution with bone morphogenetic protein-2 to obtain a composite coating solution; 4) The composite coating liquid is applied to the surface of the absorbable substrate and then freeze-dried under vacuum to obtain an absorbable bone plate with osteoinductive activity.
7. The preparation method according to claim 6, characterized in that, Step 1) The melt blending temperature is 170~190℃ and the rotation speed is 80~120 rpm.
8. The preparation method according to claim 6, characterized in that, Step 2) The buffer solution includes PBS buffer; The concentration of Bletilla striata polysaccharide in the solution is 20-50 g / L.
9. The preparation method according to claim 6, characterized in that, Step 4) The vacuum freeze-drying temperature is -50~-40℃, and the vacuum freeze-drying time is 15~20h.
10. The use of the absorbable bone plate according to any one of claims 1 to 5 or the absorbable bone plate prepared by any one of claims 6 to 9 in the preparation of fracture repair materials.